Hubungan Mutu Pelayanan KIA (Kehandalan) Dengan Kepuasan Ibu Bersalin Secara Normal Di Puskesmas Lalang Kecamatan Medang Deras Kabupaten Batubara - Yesica Geovany Sianipar; Sonia Novita Sari; Ariska Fauzianty; Friza Novita Sari (STIKes Ibnu Sina Ajibarang, 2023)
The quality of health services is degree of perfection of health services in accordance with professional standards by using the potential resources available at the public health center. Various efforts have been made by health workers at the Lalang Health Center, Medang Deras District, Batu Bara Regency, such as training for delivery assistance according to Standard Operational Procedures in improving the quality of Maternal and Child Health Services, but there are patient complaints about the quality of Maternal and Child Health Services at the Lalang Health Center, Batu Bara Regency. The purpose of this study was determine the effect of the quality Maternal and Child Health Services on maternal satisfaction in normal delivery at the Lalang Health Center, Medang Deras District, Batu Bara Regency. This research is an analytic study using a cross sectional design, sample of 59 people by simple random sampling. The analysis was carried out in univariate and bivariate with chi square test p-value <0.05. The results of this study indicate that there is a significant relationship between quality Maternal and Child Health Services (reability) on maternal satisfaction in normal delivery at the Lalang Health Center, Medang Deras District, Batu Bara Regency, with a p value <0.05 (0.034).